Arts integration and special education an inclusive theory of action for student engagement - Anderson, Alida (New York Routledge, 2015)
"Arts Integration and Special Education contributes to research, policy, and practice by providing a theory of action for studying how linguistic, cognitive, and effective student engagement relates to arts integrated learning contexts and how these dimensions of engagement influence content area and literacy learning. Arts Integration and Special Education connects the interdisciplinary framework in human development and linguistics, special education, and urban education with primary action research by special educators trained in arts integration, working in an inclusive urban charter school with middle school age students. Upper elementary to middle-grade level student learning is relatively understudied and this work contributes across fields of special education and urban education, as well as arts education. Moreover, the classrooms in which the action research occurs are comprised of students with a diverse range of abilities and needs. The book's interdisciplinary model, which draws on developmental and educational psychology, special education, and speech/language pathology research and practice, is the first to posit explanations for how and why AI contexts facilitate learning in students with language and sensory processing disorders, and those at-risk for school failure due to low socioeconomic status conditions"--Provided by publisher.
Part I: Theoretical and methodological issues in the study of arts integration in education -- Chapter 1: A historical review of arts integration research and practice: lessons learned / Sandra M. Loughlin and Alida Anderson -- Chapter 2: Arts integration as a contextualized language learning environment / Alida Anderson -- Chapter 3: Cognitive and Affective Engagement, Arts Integration, and Students with Disabilities / Katherine A. Berry and Sandra M. Loughlin -- Chapter 4: Understanding how and why arts integration engages learners / Alida Anderson -- Part II: Arts integration demonstrations of practice in inclusive classrooms -- Chapter 5: Film arts integration and literature study: influences on engagement / Kristin Nagy and Alida Anderson -- Chapter 6: Process drama arts integration and social studies: influences on engagement christina / Bosch and Alida Anderson -- Chapter 7: Dance/movement arts integration and mathematics: influences on engagement / Robyne Davis and Alida Anderson -- Part III: Reflections and next steps for arts integration research and practice -- Chapter 8: Where are we now: the research on arts integration and special education / Jean B. Crockett, Katherine A. Berry, and Alida Anderson -- Chapter 9: Where are we going? trajectories for research on the arts and special education / James S. Catterall.
Includes bibliographical references and index.
Keywords: Special education -- Art